(untitled) (Management and Connections Journal, 2013)
DOI: http://dx.doi.org/10.13071/regec.2317-5087.2013.2.1.4460.187-209. In order to cope with the many changes experienced by the sector, the pharmaceutical companies in the retail market have as an alternative the amplified offer of higher quality services, besides developing long-term relationships with their customers. This paper analyzes the client’s perception on the service provided by pharmacies, as well as aspects related to customer loyalty in retail pharmacist. Thereunto, we carried out a survey with questionnaires in a sample of the non-probability by quota type (age and region) of 196 clients of pharmacies located in Vitória-ES/Brazil. Data analysis was performed using the software SPSS and EXCEL. It was found that the aspects “low prices” and “location of pharmacy” are the most relevant to both loyal and non-loyal customers. It was also concluded that the loyalty-cards can be a strategy used by companies to add value to their business, but cannot be an indicator or instrument of customer loyalty.